Tingkat Kepercayaan Masyarakat Terhadap Kepemimpinan Kepala Desa Dalam Dinamika Masa Jabatan 8 Tahun - Padilah, Ahirul Habib; Patriani, Ira; Ritaudin, Ritaudin; Nazari, Nada Azwa; Apriyani , Eka (Indonesian Journal Publisher, 2025)
This research investigates the level of community trust in village heads within the contexts of 6-year and 8-year terms in Indonesia. Employing a qualitative approach, the study focuses on leadership theory and trust as its analytical framework. Research methods include in-depth interviews with village community members and participatory observation to gather deep, contextual data. Findings reveal significant differences in perceptions and trust towards village heads between the 6-year and 8-year terms. Extended terms provide greater opportunities for village heads to build stronger relationships, increase community participation, and plan long-term village development. Conversely, shorter terms place pressure on village heads to perform quickly and effectively. The implications of this research underscore the importance of leadership continuity, policy transparency, and community participation in fostering sustained trust at the village level.